Efficiency enhancement of non-fullerene organic solar cells using PEDOT:PSS diluted with alcohol solvents as the hole transport layer - Han, Tingting; Gao, Chuanlin; Sun, Kangbo; Zhu, Liangxiang; Wang, Lihong; Liang, Wenting; Miao, Yanqin; Wang, Yufei; Qiu, Mingxia; Li, Shunpu; Zhang, Guangye (Frontiers in Materials, 2024)
The poly3,4-ethylenedioxythiophene) poly(styrene sulfonate) (PEDOT:PSS) hole transport layer (HTL) has always played a crucial role in achieving high-efficiency organic solar cells (OSCs) owing to its unique advantages of suitable energy levels and high optical transparency. However, the inherent insulation and easy aggregation property of PSS results in relatively low conductivity and high surface roughness of the PEDOT:PSS film, which is unfavorable for charge transport and the morphology of the top layer. To address these problems, we use PEDOT:PSS diluted in a series of alcoholic solvents and evaluate them on the PM6:Y6 system. Among these, the PM6:Y6 devices using PEDOT:PSS modified with ethanol as the HTL demonstrate the best vertical phase segregation and carrier extraction. In addition, the PEDOT:PSS film with added ethanol also has the smoothest surface compared to those diluted in the other alcoholic solvents. Finally, a high power conversion efficiency of 18.13% was obtained with the PM6:Y6 devices based on PEDOT:PSS modified by ethanol. This work provides a sufficient reference for the alcoholic modification of PEDOT:PSS and also proposes a feasible solution for high-efficiency OSCs.